Identification and characterization of two salmon louse heme peroxidases and their potential as vaccine antigens - Elisabeth Gislefoss; Amr Ahmed Abdelrahim Gamil; Aina-Cathrine Øvergård; Øystein Evensen (iScience, 2023)
Summary: Salmon louse, Lepeophtheirus salmonis, represents major challenge for salmon farming. Current treatments impose welfare issues and are costly, whereas prophylactic measures are unavailable. Two salmon louse heme peroxidases (LsPxtl-1 and LsPxtl-2) were tested for their importance for parasite development and as potential vaccine candidates. LsPxtl-1 possesses two heme peroxidase domains and is expressed in ovaries and gut, whereas LsPxtl-2 encodes one domain and contains N-terminal signal peptide and an Eph receptor ligand-binding domain. LsPxtl-1, but not LsPxtl-2, knockdown in nauplius II stage caused poor swimming and death, indicating its importance for parasite development. Immunizations using single DNA plasmid injection encoding the peroxidases or heterologous prime (DNA) and boost (recombinant LsPxtl-2 protein) gave non-significant reduction in lice numbers. Single injection gave low specific antibody levels compared with the prime-boost. The findings suggest LsPxtl-1 is important for parasite development but formulations and vaccination modalities used did not significantly reduce lice infestation.